2017
DOI: 10.1111/rda.13006
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction regime in a rabbit line selected for growth rate alters oocyte maturation manifested by alteration in MSY2 gene expression

Abstract: Young rabbit females selected for growth rate may have nutritional needs, which may not be met with the common practice of feed restriction during rearing in commercial rabbit production. The aim of this study was to analyse whether two different feeding programmes: ad libitum or restricted (130 g/day) feeding, applied in young rabbit females for 1 month at the end of rearing, could modulate the origin of ovulation process and the quality of the oocytes. At 16 weeks of age, 34 females were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Furthermore, PIK3R1 is also involved in signaling pathways that control GC proliferation and oocyte maturation ( Zheng et al, 2012 ). EGFLAM is involved in cellular growth, differentiation, and proliferation ( Naturil-Alfonso et al, 2017 ), but Vicente et al (2013) found that expression of EGFLAM is negatively correlated with foetal growth. Herein, expression of EGFLAM levels was lower in the RL group, demonstrating a negative correlation with follicle maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PIK3R1 is also involved in signaling pathways that control GC proliferation and oocyte maturation ( Zheng et al, 2012 ). EGFLAM is involved in cellular growth, differentiation, and proliferation ( Naturil-Alfonso et al, 2017 ), but Vicente et al (2013) found that expression of EGFLAM is negatively correlated with foetal growth. Herein, expression of EGFLAM levels was lower in the RL group, demonstrating a negative correlation with follicle maturation.…”
Section: Discussionmentioning
confidence: 99%
“…PIK3R1 plays an important role in regulating ovarian activities in yak seasonal reproduction [45]. EGFLAM is involved in cellular growth, differentiation and proliferation, including angiogenesis and membrane fusion [46]. Competing endogenous RNAs (ceRNAs) analysis revealed that circRNAs can compete with miRNAs to alter the expression of key genes involved in GC differentiation and follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a rabbit line selected for growth rate, Naturil- Alfonso et al (2016) observed worse reproductive performance results (-0.2 kindling rate, +0.18 and +0.29 gestational and foetal losses and -1.6 kits during the first three reproductive cycles) when rabbit does were restricted (130 g/d) for a month before being mated. However, in other studies done with the same scheme and line, the differences in reproductive performance disappeared (Naturil-Alfonso et al, 2017). In maternal crossbreed females, Martińez-Paredes et al (2012) observed that a restriction of 140 g/d from 12 wk of age, with a flushing 4 d before mating (18 wk of age), led young rabbit does to show an energy intake below to the recommendations (Xiccato and Trocino, 2010), causing a delay in body development compared to those fed ad libitum.…”
Section: Rearing Feeding Programmes: Concentrate Dietsmentioning
confidence: 94%